Autocrine negative feedback regulation of lipolysis through sensing of NEFAs by FFAR4/GPR120 in WAT - Anna Sofie Husted; Jeppe H. Ekberg; Emma Tripp; Tinne A.D. Nissen; Stijn Meijnikman; Shannon L. O'Brien; Trond Ulven; Yair Acherman; Sjoerd C. Bruin; Max Nieuwdorp; Zach Gerhart-Hines; Davide Calebiro; et al. (Elsevier, 2020)
Objectives: Long-chain fatty acids (LCFAs) released from adipocytes inhibit lipolysis through an unclear mechanism. We hypothesized that the LCFA receptor, FFAR4 (GPR120), which is highly expressed in adipocytes, may be involved in this feedback regulation. Methods and results: Liquid chromatography mass spectrometry (LC-MS) analysis of conditioned media from isoproterenol-stimulated primary cultures of murine and human adipocytes demonstrated that most of the released non-esterified free fatty acids (NEFAs) are known agonists for FFAR4. In agreement with this, conditioned medium from isoproterenol-treated adipocytes stimulated signaling strongly in FFAR4 transfected COS-7 cells as opposed to non-transfected control cells. In transfected 3T3-L1 cells, FFAR4 agonism stimulated Gi- and Go-mini G protein binding more strongly than Gq, effects which were blocked by the selective FFAR4 antagonist AH7614. In primary cultures of murine white adipocytes, the synthetic, selective FFAR4 agonist CpdA inhibited isoproterenol-induced intracellular cAMP accumulation in a manner similar to the antilipolytic control agent nicotinic acid acting through another receptor, HCAR2. In vivo, oral gavage with the synthetic, specific FFAR4 agonist CpdB decreased the level of circulating NEFAs in fasting lean mice to a similar degree as nicotinic acid. In agreement with the identified anti-lipolytic effect of FFAR4, plasma NEFAs and glycerol were increased in FFAR4-deficient mice as compared to littermate controls despite having elevated insulin levels, and cAMP accumulation in primary adipocyte cultures was augmented by treatment with the FFAR4 antagonist conceivably by blocking the stimulatory tone of endogenous NEFAs on FFAR4. Conclusions: In white adipocytes, FFAR4 functions as an NEFA-activated, autocrine, negative feedback regulator of lipolysis by decreasing cAMP though Gi-mediated signaling.